Identifying & linking corporate entrepreneurial characteristics to innovation - Thomas, Robin Luke (2010)
Prominent academicians, investors and successful entrepreneurs would unanimously agree that the terms “Entrepreneur” and “Innovation” are undoubtedly the most important determinants in the new knowledge economy. Unfortunately, empirical and theoretical understanding of the influence of the entrepreneur on innovation has long been stymied. Studies of entrepreneurial characteristics have failed to demonstrate convincing links with entrepreneurial states of being, though studies of the former have shown morepromise than have those of the latter. In an attempt to explain the failure to link entrepreneurial characteristics with innovation within an organization and thus to stimulate and modify research agendas, this management project investigates corporate entrepreneurs within a public listed company and derives therefore the most agreed upon characteristics for a corporate entrepreneur to innovate. This derivation draws upon current corporate entrepreneurship and innovation theory amongst corporate leaders acting as entrepreneurs within the selected organization. Though there is considerable controversy in the field of psychology concerning the ability of personality traits to explain behavior, it is accepted by many that such traits do exist, that they are stable over time, and that they explain behaviors if the level of aggregation is wide enough. It is noted that the problem in using personality traits to explain innovation was that such traits are mediated by motivation and moderated by abilities in their causal connection to performance. Thus personality traits are somewhat removed from performance in the causal chain of events. Hence, this research rather redefines this emerging model of “Corporate Entrepreneurial characteristics that lead to Innovation” by drawing upon previous critiqued literature and research findings. The literature suggests that “entrepreneurial characteristics” and the context in which it is used forms the foundation for entrepreneurial management and innovation. The intent behind this research is to identify specific characteristics that can be studied or acted upon (in an applied sense) to improve the chances of innovation in an organization. This research should provide an impetus to put the corporate entrepreneur into a central position in entrepreneurial study.